THE EFFECTS OF FRENCH COLONIAL FISCAL AND BANKING POLICIES ON ALGERIAN SOCIETY (1830–1900) - Mabrouk Mouhoub; Abdelhai Abdelhafid (International Journal of Innovative Technologies in Social Science, 2025)
The French colonial policy in Algeria, from its very beginnings, constituted a fully integrated strategy to reshape this colony according to the capitalist system. If the military control opened the door for the presence of the colons, the consolidation of this presence was not possible without a strong financial and banking system, which aimed at redirecting the country’s resources and preparing an economic environment that serves the settlement project. Thus, during the second half of the nineteenth century, France sought to establish a financial pillar based mainly on heavy taxation imposed on the natives, as a preliminary step to serve the settlers. In parallel with that, it established a banking system that took charge of financing the settlement projects, by providing loans and financial facilities that aimed to entrench the European presence in Algeria.